Union Raiding and Organizing in Ontario - Bartkiw, Timothy; Martinello, Felice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2005)
This paper provides the first analysis of aggregate raiding activity in Ontario by isolating raid applications from available certification data. Raiding in Ontario generally decreased over the 1975 to 2003 period save for the huge increases in 2000 and 2001 involving the CAW and SEIU. Bargaining units are significantly larger in raids, and legislative changes had little effect on aggregate raiding levels. Over most of the period raiding activity has been quite modest. Thus analyses of union organizing and its effect on union density are unlikely to be affected by leaving raids in the organizing data. An important exception occurs in 2000 and 2001, where the certification data seriously overstate new organizing. Corrected measures show that new (non-raid) union organizing continues to decline in Ontario. The decline in new organizing has been greater than the decline in raiding, resulting in an increased proportion of organizing due to raids in recent years.